Effect Of sodium glucose co-transporter 2 inhibitors on weight reduction in overweight and obese population: A review - Mahin, Md. Tamjidur Rahman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.